KAJIAN KLASIFIKASI TANAH DI NAGARI SUNGAI KAMUYANG KECAMATAN LUAK KABUPATEN LIMAPULUH KOTA - Dyah Puspita Sari; Azwar Rasyidin; Amrizal Saidi; J Juniarti (Jurnal Tanah dan Sumberdaya Lahan, 2020)
This study was aimed to examine the classification of soil in Nagari Sungai Kamuyang, Luak District, Limapuluh Kota Regency by the USDA Soil Taxonomy up to the level of family and synchronized with the National Soil Classification. This study was conducted in Nagari Sungai Kamuyang. Soil analysis conducted at the Laboratory Soil Department Faculty of Agriculture Andalas University, Soil Chemistry Laboratory and the Mineralogy Laboratory of Soil Research Institute in Bogor. This study used a survey method with purposive sampling random sampling based on unit land. This study consisted of preparation, pre-survey, the main survey, laboratory analysis, and data processing. Based on the results of research on the study of the soil classification in Nagari Sungai Kamuyang, Luak District, Limapuluh Kota Regency, showed soil classification based on Soil Taxonomy on the profile 1 was classified as the Ordo: Inceptisols, Sub Ordo: Udepts, Great Group: Dystrudepts, Sub Group: Andic Dystrudepts, Family: Fine Dust, Kaolinite, Isohypertermik, Andic Dystrudepsts. The profile 2 was classified as an Ordo: Andisols, Sub Ordo: Udands, Great Group: Hapludands, Sub Group: Typic Hapludands, Family: Medial, Amorfik, Isohypertermik, Typic Hapludands. Based on the National Soil Classification, profile 1 was classified as Type: Latosol, Various: Latosol Umbrik. Profile 2 was classified as Type: Andosol, Various: Andosol District.